Penerapan Bimbingan Kelompok untuk Meningkatkan Motivasi Belajar Bimbingan Konseling Peserta Didik SMP Negeri 4 Mataram - Siti Zuhaerani (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2021)
This study aims to determine the effectiveness of the implementation of group guidance in increasing the motivation to learn counseling guidance for students of SMP Negeri 4 Mataram. This research method uses classroom action research conducted in two cycles. The research instrument used observation and documentation. The data analysis technique used descriptive analysis. The results showed that in cycle II the indicators of the success of this study have been proven. So it can be concluded that the application of group guidance can increase the motivation to learn counseling guidance for class VIII.2 students of SMP Negeri 4 Mataram.